Genome-Wide Association Study of Growth and Feeding Traits in Pekin Ducks - Zhu, Feng; Cheng, Si-Rui; Yang, Yu-ze; Hao, Jin-Ping; Yang, Fang-Xi; Hou, Zhuo-Cheng (Frontiers in Genetics, 2019)
Growth rate and feeding efficiency are the most important economic traits for meat animals. Pekin duck is one of the major global breeds of meat-type duck. This study aims to identify QTL for duck growth and feeding efficiency traits in order to assist artificial selection. In this study, the growth and feeding related phenotypes of 639 Pekin ducks were recorded, and each individual genotype was evaluated using a genotyping-by-sequencing (GBS) protocol. The genetic parameters for growth and feeding efficiency related traits were estimated. Genome-wide association analysis (GWAS) was then performed for these traits. In total, 15 non-overlapping QTLs for the measured traits and 12 significant SNPs for feed efficiency traits were discovered using a mixed linear model. The most significant loci of feed intake (FI) is located in a 182Mb region on Chr1, which is downstream of gene RNF17, and can explain 2.3% of the phenotypic variation. This locus is also significantly associated with residual feed intake (RFI), and can explain 3% of this phenotypic variation. Among 12 SNPs associated with the feed conversion ratio (FCR), the most significant SNP (P-value=1.65E-06), which was located in the region between the 3rd and 4th exon of the SORCS1 gene on Chr6, explained 3% of the phenotypic variance. Using gene-set analysis, a total of two significant genes were detected in three different QTL regions on Chr1. This study is the first GWAS for growth and feeding efficiency related traits in ducks. Our results provide a list of candidate genes for marker assisted selection for growth and feeding efficiency, and also help to better understand the genetic mechanisms of feed efficiency and growth in ducks.